Kasus Iskemia Tungkai Akut yang Tidak Terduga pada Pasien Sindrom Nefrotik - Erickatulistiawan, Gallusena; Tjahjono, Cholid; Kurnianingsih, Novi (Jurnal Klinik dan Riset Kesehatan, 2024)
Background: Acute Limb Ischemia ALI requires urgent intervention to avert irreversible tissue damage, with treatment complexity increasing in patients with nephrotic syndrome. Case Presentation: A 23-year-old female with nephrotic syndrome presented acute right leg pain. Examination showed erythema and a cold sensation in the affected leg. Ultrasound revealed no blood flow in certain leg arteries. Despite multiple thrombectomies and heparin treatment, only minimal improvement was observed. The patient underwent a below-knee amputation after unsuccessful attempts to restore blood flow. Her condition worsened with new vascular occlusions, requiring Catheter Direct Thrombolysis CDT. Post-CDT, she suffered severe bleeding, hemorrhagic shock, cardiac arrest, and multi-organ complications, leading to her death on treatment day 35. Discussion: This case illustrates the complexities of managing ALI in patients with nephrotic syndrome, which increases hypercoagulability and vascular complication risks. It highlights the need for an integrated nephrology and vascular approach, considering the high risks of hemorrhagic and thrombotic complications. A comprehensive and multidisciplinary treatment strategy is crucial, especially with vigilant monitoring for severe complications like infection and sepsis, to enhance treatment outcomes in similar cases. Conclusion: This case of a 23-year-old woman with ALI and nephrotic syndrome presented significant treatment challenges. Despite numerous interventions, including thrombectomies and CDT, severe complications ensued, emphasizing the need for comprehensive management and further research in similar complex conditions.